E-MONEY DITINJAU DARI DIMENSI MAQĀṢID AL-SYARĪ - Sayuti, Muhammmad Noor; Wijaya, Wijaya (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
The increasing popularity of technology-based pasyment system substanstially changes conventional payment system design from cash payment system to non-cash payment system. Gradually, the expansion is impressive enough to change paradigm of economist in micro-transaction settlement, as well as becoming the root of Less Cash Society spirit creation.One of the instruments of non-cash payment which has been a trend today is E-money.It is an electronic-based non-cash payment. Some studies showed that there was a positif impact to monetery policy earned from this trend, its influence in the level of velocity of money and the effort to reduce the use of cash payment as an effort to hold inflation flow. The purpose of this study is to find out maqāṣid al-syarī